Potensi Makroalga di Paparan Terumbu Karang Perairan Teluk Lampung - Tri Handayani (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
The Potency of Macroalgae in the Reef Flat of Lampung Bay. Lampung Bay is a strategic area that develops quite rapidly. This condition will put pressure on the coastal ecosystem as the estuary of all activities from surrounding areas. Macroalgae, which is one component of the coastal ecosystem, is also under pressure. Therefore, we need to know the species richness, potency, and macroalgae life characteristics in Lampung Bay waters. The study was conducted in March 2009, in eight locations, namely Piabung, Klagian, Pancur, Limbungan, Puhawang Barat, Puhawang Timur, Puhawang Kecil, and Kalangan. The macroalgae samples were collected by the quadratic transect method. The parameters observed were species, biomass, substrate, and macroalgae life form. A total of 27 macroalgae species were identified consisting of three divisions and 17 genera. Division Chlorophyta, Ochrophyta, and Rhodophyta each consisted of nine species. Nineteen species were macroalgae that have important economic values. The highest number of macroalgae species was found in Pancur, while the lowest was in Kalangan. The genera that dominated the study sites were Halimeda and Caulerpa. The highest average biomass was found in Pancur with 675.5 g/m2, whereas in Kalangan there was no macroalgae observed. The base substrate was dominated by sand. The condition of the base substrate affects the number of species and the nature of macroalgae life. In general, macroalgae resources in the waters of Lampung Bay are not potential to be developed, but Sargassum in Pancur has the potential to be developed as seeds.